2009
DOI: 10.1111/j.1547-5069.2009.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Among HIV‐Positive Pregnant Women in Thailand

Abstract: Depressive symptoms have been associated with faster progression to acquired immunodeficiency syndrome among HIV-positive individuals. The high rate of depression in our study suggests that HIV-positive pregnant women in Thailand should all be screened for depressive symptoms. Causes of physical symptoms should be identified and treated. Emotional support and self-esteem should be strengthened for HIV-positive pregnant Thai women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…In contrast, other research has demonstrated significantly higher rates of depression among women with HIV (e.g., Chaudron, 2010;Ciesla & Roberts, 2001;Kapetanovic et al, 2014;Ross et al, 2009). Untreated depression during pregnancy has been correlated with an increased risk for postpartum depression and adverse maternal and infant health outcomes, irrespective of HIV serostatus (Alder, Fink, Bitzer, Hosli, & Holzgreve, 2007;Field, 2011;Marcus, 2009), including negative consequences for the emotional, behavioral, and cognitive development of the child (Beck, 1995(Beck, , 1998O'Connor, Heron, Golding, Beveridge, & Glover, 2002;Ryan, Milis, & Misri, 2005;Sohr-Preston, 2006).…”
Section: Women With Human Immunodeficiency Virus (Hiv) Represent Nearmentioning
confidence: 78%
See 2 more Smart Citations
“…In contrast, other research has demonstrated significantly higher rates of depression among women with HIV (e.g., Chaudron, 2010;Ciesla & Roberts, 2001;Kapetanovic et al, 2014;Ross et al, 2009). Untreated depression during pregnancy has been correlated with an increased risk for postpartum depression and adverse maternal and infant health outcomes, irrespective of HIV serostatus (Alder, Fink, Bitzer, Hosli, & Holzgreve, 2007;Field, 2011;Marcus, 2009), including negative consequences for the emotional, behavioral, and cognitive development of the child (Beck, 1995(Beck, , 1998O'Connor, Heron, Golding, Beveridge, & Glover, 2002;Ryan, Milis, & Misri, 2005;Sohr-Preston, 2006).…”
Section: Women With Human Immunodeficiency Virus (Hiv) Represent Nearmentioning
confidence: 78%
“…Pregnancy is a time of increased vulnerability for depression and anxiety in general (Gaynes et al, 2005;Ross & McLean, 2006;Viguera et al, 2011). Although high rates of depression and other mental health vulnerabilities have been reported in women with HIV in general (Basu, Chwastiak, & Bruce, 2005;Morrison et al, 2002) and during pregnancy (Kapetanovic et al, 2009, Kapetanovic, Dass-Brailsford, Nora, & Talisman, 2014Ross, Sawatphanit, & Zeller, 2009), there is a gap in the field of evidence regarding mental health in the perinatal period for women with HIV infection.…”
Section: Women With Human Immunodeficiency Virus (Hiv) Represent Nearmentioning
confidence: 97%
See 1 more Smart Citation
“…In Thailand, researchers have reported that depression, shame, and suicidal ideas are common among seropositive pregnant women and seropositive mothers of young children (Bennetts et al, 1999;Ross & Srisaeng, 2005). In a study of 129 HIV-infected Thai mothers of 18-24-month-old children, 43% showed depressive symptoms and 77% perceived their HIV infection as being shameful for their family (Bennetts et al, 1999).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…Women diagnosed with HIV in both developing and developed countries often manifest psychological distress, including low self-esteem, fear, anxiety, depression, and suicidal ideas (e.g., Catalan, 2000;Chandra, Ravi, Desai, & Subbakrishna, 1998;Green, Ardron, & Heath & Rodway, 1999;Loriz-Lim, 1995;Lyon & Younger, 2001;Maj, 1997;Palyo, 1995;Ross & Srisaeng, 2005;Withell, 2000). Among 955 seropositive women and men who lived in Brazil, Germany, Kenya, Thailand, and Zaire, many experienced depression, and those who had more physical problems showed more depressive symptoms than those with fewer physical problems (Maj, 1997).…”
Section: Review Of the Literaturementioning
confidence: 98%